Onkologische Bewegungsmedizin: auf dem Weg zur Standardsäule der Versorgung von Krebspatienten - Baumann, Freerk T.; Wiskemann, Joachim (Der Onkologe, 2017)
Numerous high-quality clinical trials, systematic reviews and meta-analyses have proven the beneficial effects of exercise interventions in cancer patients across all stages of cancer treatment. In addition to the positive effects of exercise on treatment-related side effects, physical activity appears to improve the health-related quality of life in cancer patients. Exercise programs also increase adherence to chemotherapy, which allows cancer patients to better tolerate cancer treatment. Moreover, recent data from patients with breast and colon cancer suggest that cancer-specific and overall mortality may be reduced through participating in regular physical activity. Aside from the many unanswered questions regarding the optimal dosage of physical activity for cancer patients, as well as the utility of exercise programs for patients with advanced cancers, there is a need to integrate exercise programs into cancer care in Germany.